Revolutionizing Disease Prevention: The Rise of mRNA Vaccines and Nanotechnology for the Treatment of Cancer and Infectious Diseases - Shankar, Diksha; Mishra, Deepak; Singh, Astha; Pathak, Neha; Minocha, Neha; Pandey, Parijat; Malhotra, Pankaj (Current Nanomedicine, 2025)
<span class=
Keywords: nanotechnology